THE PSYCHOLOGICAL TRAUMA EXPRESSIONS OF CHILDREN LIVING IN THE NON-INTERGRITY FAMMILY THROUGH EMOTIONS AND FEELINGS REGARDING FAMILY AND SOCIAL LIFE - Huỳnh Văn Sơn; Nguyễn Thị Diễm My; Giang Thiên Vũ; Đặng Vũ Khoa (Tạp chí Khoa học Đại học Đà Lạt)
The article addresses the expression of psychological trauma of children living in the non-integrity family through emotions and feelings of children regarding family and social life. The results show that there is a difference between the psychological and emotional trauma of three groups of children: “no psychological trauma”, “boundary state” and “psychological trauma in the non-integrity family”. In particular, children with psychological trauma in the non-integrity families have more negative emotions regarding family and social life than the other two groups. The statistics also show that the emotional expression of children regarding family and social life differs by education level (Sig. = 0.005).